Host and abiotic constraints on the distribution of the pine fungal pathogen Sphaeropsis sapinea (= Diplodia sapinea) - Roy, Julien; Kyritsi, Ioanna; Reinwarth, Nadja; Bachelier, Julien B.; Rillig, Matthias C.; Lücking, Robert (Frontiers in Forests and Global Change, 2022)
Plant fungal pathogens are an increasing emerging threat as climate change progresses. Sphaeropsis sapinea (syn. Diplodia sapinea), the causal fungal agent of Diplodia tip blight, is a major pathogen of pines of forestry and ornamental relevance in Europe and worldwide. Here, we combined molecular-based field surveys in a common-garden setting and across an elevational gradient with historical records, cultivation-based growth experiments and microscopy to report on host and abiotic constraints on the distribution of S. sapinea. Using the arboretum at the Botanical Garden Berlin, Germany, to control for environmental variability, S. sapinea was detected on all seven host Pinus species we studied. However, P. sylvestris is the only species in which the fungus was detected in symptomless needles at the arboretum, and the most frequently recorded host for over a century, suggesting that it is the main, and perhaps, potential original host. In addition, sampling symptomatic needles in 4 out of the 7 same species across a gradient from 200 to 2100 metres of elevation in the French Alps, S. sapinea was not detected at elevation higher than 800 m. Abiotic constraints were also supported by reduced growth of isolates of S. sapinea at low temperature under controlled conditions, but a 35°C prior stress exposure increased the subsequent growth of S. sapinea within its optimal temperature range (20-30°C). Altogether, our study thus not only suggests that S. sapinea is more likely to cause tip blight in P. sylvestris compared to the other species we studied, but also that in the current context of global climate change with predicted temperature increases, the fungus could infect a wider range of pine hosts and locations worldwide.